Italian Hydrocarbon Upstream: Report on the State and Safety of the Offshore Activities (years 2016-2023) - Matteo Iaiani; Paolo Macini; Alessandro Tugnoli; Valerio Cozzani; Ezio Mesini (Chemical Engineering Transactions, 2024)
Exploration, drilling, production, transportation, and logistics in offshore environment play a crucial role in the global energy sector, contributing substantially to the world's oil and gas supply. Ensuring safe offshore operations is key requirement for the social acceptability of offshore activities. The Legislative Decree n. 145/2015 (Italian transposition of the European Directive 2013/30) has established the creation of a Competent Authority responsible for overseeing and coordinating various aspects related to maritime safety as a multi-branch structure which comprises key representatives from various public bodies. This article will delve into key aspects of offshore activities and their safety performance. The available data (years from 2016 to 2023) on offshore operations in the Italian offshore are analysed using specifically developed key performance indicators. The data includes the number and type of offshore installations, total offshore working hours, total oil and gas production rates, reported inspections conducted offshore. Data on past undesirable events occurred in Italian offshore installations were also analysed. Through the examination of these quantitative indicators, the article aims to provide a comprehensive insight of the state and safety of the Italian offshore hydrocarbon upstream activities, crucial for stakeholders, regulators, and industry.